Capnocytophaga canimorsus as Cause of Fatal Sepsis. (23rd May 2019) - Hundertmark, Moritz; Williams, Tatjana; Vogel, Anja; Moritz, Maria; Bramlage, Peter; Pagonas, Nikolaos; Ritter, Oliver; Sasko, Benjamin
Abstract : A rare consequence of dog bites is the infection with Capnocytophaga canimorsus, and only a few cases have been documented. We describe a 41-year-old, formerly healthy woman who died from septic shock and multiorgan failure. It is the first case of a young individual without obvious immunosuppression.